Manifestation of Convenience in Financial sustainability through Seerah of the Prophet Muhammad (peace be upon him) - Dr Farhana Mehmood,; Nazli Nouman, (Seerat Studies, 2023)
Financial matters required much care and responsibility in sustainable transactions, but sometimes due to strict policies individuals and companies encounter with frustration and exasperation while unnecessary complexities and obstacles in dealing with financial policies. This problem arises universally to all humanity. The present research is an endeavour to explore practicle model of financial sustainabity derived through Seerah of the Prophet. Seerah provides Prophetic policies that demonstrate leniency in the commercial transactions, and seeking the return of their funds, are deserving of Allah's mercy and acquire financial sustainability.This phenomenon involves the development of a preference for convenience, leniency, and moral goodness in the attitude and interactions of the community based on the teachings of the Prophet. Social lubrication refers to the phenomenon that facilitates smoother interactions and communication within social settings.